Code Parameter Summarization Based on Transformer and Fusion Strategy - Fanlong Zhang; Jiancheng Fan; Weiqi Li; Siau-cheng Khoo (IET Software)
Conclusion: We recommend developers employ our approach as well as the fusion strategies to produce parameter summaries to enhance the comprehensibility of code.